Therapeutic potential of formononetin in cirrhotic portal hypertension: modulating hepatic fibrosis, macrophage polarization, and lymphangiogenesis - Wu, Zhenghao; Luo, Guqing; Li, Hongjie; Chen, Min; Wu, Guangbo; Fan, Qiang; Zhang, Chihao; Yu, Jiwei; Lin, Jiayun; Zhao, Jinbo; Qi, Xiaoliang; Huo, Haizhong; et al. (Frontiers in Immunology, 2025)
IntroductionFormononetin regulates intrahepatic fibrogenesis and macrophage polarization to improve portal pressure and liver function in rats with cirrhotic PHT through SMAD3, STAT1, STAT3 and GSK-3β signaling pathways, and modulates lymphangiogenesis through direct action and macrophage polarization-mediated indirect effects. Formononetin has the potential function of treating cirrhotic PHT.Background and aimsFormononetin (FN) has been reported to have anti-fibrotic effects in the kidneys and anti-M1 polarization effects on macrophages. Lymphangiogenesis is closely associated with macrophages, but its role in cirrhosis and portal hypertension (PHT) remains unclear. This study aims to explore the effects of FN on cirrhotic PHT and the disease-related intrahepatic lymphangiogenesis.MethodsIn vivo experiments, bile duct ligation (BDL) induced PHT models were conducted in rats, followed by a 4-week FN treatment (50 mg/kg/day) administered via gavage. Hemodynamics, liver fibrosis, infiltration and polarization of intrahepatic macrophages, as well as intrahepatic lymphangiogenesis, were observed. For in vitro experiments, hepatic stellate cells, macrophages and lymphatic endothelial cells were used to observe the multiple effects of FN.ResultsFN significantly ameliorated portal pressure in cirrhosis-induced PHT, improved liver function, and reduced liver fibrosis and hepatic stellate cell activation with decreased SMAD3 protein expression. The intrahepatic macrophage infiltration were markedly decreased, and M1-type macrophage polarization was suppressed by FN, accompanied by inhibition of STAT1, STAT3 and GSK-3β signaling pathways. In PHT models, FN reduced VEGF-C and VEGF-D levels in both the liver and blood, inhibiting intrahepatic lymphangiogenesis in portal area. In vitro, high-dose FN significantly inhibited lymphatic endothelial cell proliferation, while the pro-lymphangiogenic effect of conditioned medium from FN-treated M1 macrophages was diminished.ConclusionsFN significantly ameliorates cirrhotic PHT while reducing fibrosis, suppressing macrophage M1 polarization and inhibiting lymphangiogenesis. This may result from its modulation of multiple signaling pathways (SMAD3, STAT1, STAT3 and GSK-3β).